2015
DOI: 10.14814/phy2.12487
|View full text |Cite
|
Sign up to set email alerts
|

Lack of independent effect of type 2 diabetes beyond characteristic comorbidities and medications on small muscle mass exercising muscle blood flow and exercise tolerance

Abstract: Persons with type 2 diabetes (T2D) are believed to have reduced exercise tolerance; this may be partly due to impaired exercising muscle blood flow (MBF). Whether there is an impact of T2D on exercising MBF within the typical constellation of comorbidities (hypertension, dyslipidemia, obesity) and their associated medications has not been investigated. We tested the hypothesis that small muscle mass exercise tolerance is reduced in persons with T2D versus Controls (matched for age, body mass index, fitness, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Similarly, a more recent study (Groen et al, 2019) reported attenuated increases in leg BF and vascular conductance in T2D patients during single-leg knee extension exercise. However, it should be noted that conflicting findings have also been reported (Martin et al, 1995;Copp et al, 2010;Poitras et al, 2015). For example, Poitras et al (2015) found similar increases in forearm muscle BF during a forearm critical force test in T2D patients and controls.…”
Section: Cardiovascular Responses To Exercise In Type 2 Diabetesmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, a more recent study (Groen et al, 2019) reported attenuated increases in leg BF and vascular conductance in T2D patients during single-leg knee extension exercise. However, it should be noted that conflicting findings have also been reported (Martin et al, 1995;Copp et al, 2010;Poitras et al, 2015). For example, Poitras et al (2015) found similar increases in forearm muscle BF during a forearm critical force test in T2D patients and controls.…”
Section: Cardiovascular Responses To Exercise In Type 2 Diabetesmentioning
confidence: 91%
“…However, it should be noted that conflicting findings have also been reported (Martin et al, 1995;Copp et al, 2010;Poitras et al, 2015). For example, Poitras et al (2015) found similar increases in forearm muscle BF during a forearm critical force test in T2D patients and controls. Nonetheless, there are substantial data reporting that T2D significantly impacts the ability to properly adjust the circulation during exercise, leading to an augmented BP and reduced contracting skeletal muscle BF.…”
Section: Cardiovascular Responses To Exercise In Type 2 Diabetesmentioning
confidence: 91%
“…This ultimately results in reduced net glucose disposal and increased risk for cardiovascular disease, blindness, renal failure, nerve damage, loss of limb, and other co-morbidities [8,9]. Exercise intolerance, defined as a susceptibility to fatigue or reduced exercise capacity (VO 2Max ), has also been a disputed co-morbidity of this disease [10,11,12,13,14,15,16,17]. Skeletal muscle accounts for ~80% of glucose uptake during an insulin clamp [18] and can increase from resting levels anywhere from 20-fold (~0.25 mM/min → ~4 mM/min single leg [19]) to 50-fold [20] during exercise [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…convective O 2 delivery) impairments. However, studies have shown that muscle blood flow during small muscle mass exercise does not differ in persons with T2D when compared to individuals without T2D, but who shared traditional comorbidities (Poitras et al 2015). In…”
mentioning
confidence: 99%
“…However, studies have shown that muscle blood flow during small muscle mass exercise does not differ in persons with T2D when compared to individuals without T2D, but who shared traditional comorbidities (Poitras et al . 2015). In the current study, the delivery of O 2 to skeletal muscle, indicated by gastrocnemius blood flow, total haemoglobin, and oxyhaemoglobin, did not differ between groups at baseline or post‐SLET.…”
mentioning
confidence: 99%